2014
DOI: 10.3389/fnbeh.2014.00427
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to acute administration of a new 5-HT7-R agonist as a function of adolescent pre-treatment: phMRI and immuno-histochemical study

Abstract: LP-211 is a new, selective agonist of serotonin (5-hydroxytryptamine, 5-HT) receptor 7 (5-HT7-R), which is part of a neuro-transmission system with a proposed role in neural plasticity and in mood, cognitive and sleep regulation. Adolescent subchronic LP-211 treatment produces some persisting changes in rats' forebrain structural and functional parameters. Here, using pharmacological MRI (phMRI), we investigated the effect of acute administration with LP-211 (10 mg/kg i.p.), or vehicle, to adult rats previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Consistent with this, adult challenge with LP-211 did not lead to a differential activation of the nucleus accumbens: this accumbal stimulation by LP-211 was indeed independent on whether adult rats were adolescent-LP-211 preexposed or not (Altabella et al, 2014). On the other side, the septum was the only brain area, across the whole forebrain, actually showing (upon adult drug challenge) a differential change due to the developmental exposure: the septum did not respond to a LP-211 challenge in naive rats but displayed a strong activation due to adolescent pre-exposure to the same drug (Altabella et al, 2014). As a matter of fact, lower levels of SERT in the nucleus accumbens were indicative of a stable rearrangement: such modifications (most probably) involved neuroreceptor systems other than the 5-HT7 one.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Consistent with this, adult challenge with LP-211 did not lead to a differential activation of the nucleus accumbens: this accumbal stimulation by LP-211 was indeed independent on whether adult rats were adolescent-LP-211 preexposed or not (Altabella et al, 2014). On the other side, the septum was the only brain area, across the whole forebrain, actually showing (upon adult drug challenge) a differential change due to the developmental exposure: the septum did not respond to a LP-211 challenge in naive rats but displayed a strong activation due to adolescent pre-exposure to the same drug (Altabella et al, 2014). As a matter of fact, lower levels of SERT in the nucleus accumbens were indicative of a stable rearrangement: such modifications (most probably) involved neuroreceptor systems other than the 5-HT7 one.…”
Section: Introductionsupporting
confidence: 67%
“…However, changes in the levels of expression of the receptor itself, which was target of the pharmacological treatment, remained elusive. The only study in which we identified a persistent change in 5‐HT7 receptor (5‐HT7‐R) levels was pointing to the septum (see Altabella et al, ). Such a region, however, was outside of those areas found to display a permanent change in network connectivity (Canese et al, ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations